Endorphins and exercise. - Grossman, A (1984)
It is generally accepted that serious exercise training leads to marked menstrual irregularity and frequently complete amenorrhea in females, due to a decrease in the release of hypothalamic gonadotrophin releasing hormone (GmRH). The recent demonstration of a rise in plasma met-enkephalin during this process suggests an etiological role for endogenous opiates, but further studies in the presence of naloxone or other opiate antagonists are necessary to define the situation further. It may be relevant that naloxone does not overcome the inhibition of GnRH release seen in anorexia nervosa (Grossman et al., 1982b). In male subjects, severe exercise leads to an opiate inhibition of ventilation and catecholamine release, pari passu with a decrease in effort perception. It is probable that these are central effects of opiates, and possible that the decrement in effort perception is causally related to the partial inhibition in catecholamine response. This suggests that the capacity to undergo severe stress is modulated by endogenous peptides - an alteration in the sympathetic and adrenomedullary response to stress may also have long-term sequelae in terms of hypertension and cardiovascular damage (Brown, 1981). We have some data that demonstrate a correlation between the level of opiate inhibition (measured by naloxone-induced changes in hormone levels) and personality variables, and it is possible that interindividual variation in stress responsiveness is opiate-mediated. Of course, opiates are only a small family in a network of neuropeptides that may control cardiac and sympathetic function, including the recently isolated 'neuropeptide tyrosine'. Nevertheless, it seems increasingly likely that endogenous opiates will be seen to be important modulators of the neuroendocrine responses to stress.